The impact of terrorist attacks on cultural values as expressed in books. - Daniel Hart; I-Ming Chiu; Richard Epstein (PLoS ONE)
We assessed the effects of the 9/11/2001 terrorist attacks on the salience of moral words and phrases in the United States, Great Britain, and Spanish-speaking countries, focusing particularly on those phrases related to authority and loyalty. Our predictions were that the 9/11 attacks would increase the salience of authority phrases suggestive of disorder ("chaos", "disobedience", etc, labeled authority-vice) and decrease words and phrases suggestive of organization ("hierarchy", "obedient", etc: authority-virtue) in books published in the United States. Similarly, we anticipated that the salience of phrases consistent with fidelity to members of one's social group ("allegiance", "one for all", loyalty-virtue), would decrease, and those suggestive of social corrosion ("betrays", "back stabs", loyalty-vice) would increase. To test these predictions, we calculated the relative frequency of authority-vice, authority-virtue, loyalty-vice, and loyalty-virtue phrases, as well as those associated with other moral values, in books published in the U.S., Great Britain, and Spanish-speaking countries for each year between 1960 and 2019. A Bayesian structural time-series approach for each type of phrase provided additional support for the hypotheses for books published in the United States. Descriptive analyses suggested that the period following 9/11 was characterized by a deceleration in historical trends toward increasing use of moral vocabulary in published books. We discuss the implications of our findings for the measurement of cultural values and the impact of terrorism events on moral foundations and suggest that the encoding of these value shifts in texts is one way in which cultural effects are sustained.